Optimization the Use of Work Safety Equipment for MV. Oriental Jade Crew Members to Support Zero Accident - Nanggala, Gilang Satrya; Mudiyanto, Mudiyanto; Kristiawan, Dedy (Universitas Hang Tuah, 2024)
Work safety equipment is a tool used in work activities on ships and ship maintenance by crew members, where activities on ships have a high risk of accidents. One of the protection efforts for crew members is to optimize the use of work safety equipment to support zero accidents. The rationale for this research is that all activities on board a ship have potential and dangerous factors that allow work accidents to occur, so it is necessary to identify these potential and dangerous factors. One effort to control risk for crew members is by implementing the use of work safety equipment and implementing safety meetings. This risk control is carried out after controlling the psychology and administration of crew members, so as to create a safe working environment on board the ship. This research was carried out using qualitative methods which provide an overview of the implementation of the use of personal protective equipment. Data collection was based on observations and interviews as well as literature studies and then analyzed using the fishbone method and compared with applicable standards and regulations.